Exchange rate as a nominal anchor : is it sustainable? Evidence from the extended Cukierman-Kiguel-Liviatan credibility and reputation model - Jurek, Michał (Economics and Business Review, 2011)
The purpose of this paper is to analyze the sustainability of exchange rate nominal anchor. In order to follow through the process of establishing such an anchor, a model formulated by Cukierman, Kiguel & Liviatan (1992) is extended to capture both commitment and anti-inflationary reputation of monetary authorities. The main finding is that if the assumptions concerning complete information about the future level of exchange rate as well as perfect homogeneity of domestic and foreign government securities are overruled, the exchange rate nominal anchor can be sustained in the short-term. This is especially the case of emerging and developing economies which usually base their antiinflationary programs on exchange rate nominal anchor, due to lack of domestic monetary policy credibility. However, this policy is biased with a vicious circle: in order to build reputation, a tough commitment concerning exchange rate must be formulated, but fulfilling this commitment is extremely hard due to repeating disturbances, which can be offset only with the use of fiscal policy. In the long-term, as situation of public finances deteriorates, exchange rate nominal anchor is exposed to more and more severe shocks that eventually may lead to its breakdown. (original abstract)